Growth, Food Efficiency, and Enzyme Activities in Yellow Rasbora (Rasbora lateristriata) at Different Feeding Frequencies - Untung Susilo; Yulia Sistina; Eko Setio Wibowo; Hanan Hassan Alsheikh Mahmoud; Hana Hana; Farida Nur Rachmawati (UIN Sunan Gunung Djati Bandung, 2023)
Many studies have been conducted on the feeding frequency in fish, but there is no information on R. lateristriata. Therefore, this study aimed to determine yellow rasbora growth performance, feed efficiency, and digestive enzyme activity at different feeding frequencies. This research was conducted experimentally with four treatments and three replications. The treatments include: P1 fish were fed two times/day; P2 fish were fed three times/day; P3 fish were fed four times/day; and P4 fish were fed five times/day. In this experiment, 420 two-month-old yellow rasboras were used. The experimental results showed that body weight gain, RGR, SGR, CF, FCR, PER, body lipid & protein levels, protein and lipid retention, protease, and amylase activity were not significantly different (p>0.05) between different feeding frequencies. However, lipase and alkaline phosphatase activities differed significantly among the different feeding frequencies. Growth performance, feed efficiency, protease activity, and yellow rasbora amylase are not affected by feeding frequency between two to five times a day. Still, the highest lipase and alkaline phosphatase activity were achieved at the feeding frequency four times a day, but no effect on growth. So, feeding twice a day is considered quite efficient for the culture of yellow rasbora. The results of this study can contribute to the development of fish farming, especially the yellow rasbora, in the future.